One or two: how many species of the genus Pyrrhocorax (Passeriformes, Corvidae) inhabited the Crimea during the Late Pleistocene - Leonid, Horobets; Kovalchuk, Oleksandr; Ridush, Bogdan (Zoodiversity, 2023)
The article provides an overview of bird remains assigned to the genus Pyrrhocorax Tunstall, 1771 from nine cave sites of the Late Pleistocene and Early Holocene age within the Crimean Peninsula (Ukraine). A large sample of chough bones from the Emine-Bair-Khosar Cave (722 bones) is processed, and the results obtained are presented here for the first time. Re-identification of the remains revealed the presence of the Alpine chough Pyrrhocorax graculus in the studied region instead of two species of the genus Pyrrhocorax as previously believed. The material processed was assigned to an extinct subspecies, Pyrrhocorax graculus vetus, based on a series of measurements taken from various skeletal elements (in particular, coracoideum, humerus, ulna, radius, carpometacarpus, femur, tibiotarsus, and tarsometatarsus). The previous assumptions of the coexistence of two chough species in the Crimea during the Late Pleistocene made it possible to consider the climate in this region as relatively warm. Our results indirectly revealed that the climate of the Crimean Peninsula at the verge of the Late Pleistocene and Holocene was rather cool and therefore, unsuitable for the red-billed chough.
Keywords: Alpine chough; cave sites; bone morphology; morphometry; Quaternary; Europe